Traditional local medicines in the republic of Palau and non-communicable diseases (NCD), signs of effectiveness. (23rd February 2015) - Graz, Bertrand; Kitalong, Christopher; Yano, Victor
Abstract: Ethnopharmacological relevance: The aim of this survey was to describe which traditional medicines (TM) are most commonly used for non-communicable diseases (NCD – diabetes, hypertension related to excess weight and obesity) in Pacific islands and with what perceived effectiveness. NCD, especially prevalent in the Pacific, have been subject to many public health interventions, often with rather disappointing results. Innovative interventions are required; one hypothesis is that some local, traditional approaches may have been overlooked. Materials and methods: The method used was a retrospective treatment-outcome study in a nation-wide representative sample of the adult population (about 15, 000 individuals) of the Republic of Palau, an archipelago of Micronesia. Results: From 188 respondents (61% female, age 16–87, median 48, ), 30 different plants were used, mostly self-prepared (69%), or from a traditional healer (18%). For excess weight, when comparing the two most frequent plants, Morinda citrifolia L. was associated with more adequate outcome than Phaleria nishidae Kaneh. ( P =0.05). In case of diabetes, when comparing Phaleria nishidae ( =Phaleria nisidai ) and Morinda citrifolia, the former was statistically more often associated with the reported outcome "lower blood sugar" ( P =0.01). Conclusions: Statistical association between a plant used and reported outcome is not a proof of effectiveness or safety, but it can help select plants of interest for further studies, e.g. through a reverse pharmacology process, in search of local products which may have a positive impact on population health. Graphical abstract: